PENGARUH BAURAN PEMASARAN JASA (Product, Price, Place, Promotion, Process, people, and Physical Evidence ) TERHADAP KEPUTUSAN PEMBELIAN (Study Kasus Pada Jasa Transportasi CV King Tour And Travel) - Syamsul Ibad; Rois Arifin; Achmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2018)
AbstractThe research intends to show the effect of service marketing mix conducted by CVKing Tour and Travel simultaneously and partially to the purchasing decision oftransportation services. This research was conducted at CV King Tour and Travelcompany. This research uses descriptive quantitative with sampling technique withnon probabilty sampling technique. The type of data used in the study is the timeseries with data collection procedures through the delivery of questionnaires toselected consumers as a sample. The result of data analysis and hypothesis shows thatmarketing service mix consisting of (Product, Price, Place, Promotion, Process,People, and Physical Evidence) have a positive effect on purchasing decision. Andthat shows the significant result of each marketing mix variable that is Promotion andPhysical Evidence).Keywords: Service Marketing Mix, Purchase Decision.